Carbon-supported molybdenum nickel-based water electrolysis hydrogen evolution catalyst and preparation and application thereof

By using carbon-loaded molybdenum nickel-based catalysts in water electrolysis hydrogen production technology and using laser pulse irradiation technology to achieve the integration of four components of the material, the problem of high cost of precious metal electrocatalysts is solved, and efficient catalytic water decomposition under alkaline conditions is achieved, which significantly improves the catalytic efficiency.

CN119506947AActive Publication Date: 2025-02-25SHANGHAI HYDROLAN TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411607715.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

In the existing water electrolytic hydrogen production technology, the high cost and limited availability of precious metal electrocatalysts limit their application in large-scale industrial hydrogen production, and the catalytic performance of non-precious metal molybdenum nickel-based materials has not yet reached the level of completely replacing precious metal catalysts.

Method used

A carbon-loaded molybdenum nickel-based catalyst is used as the electrode material, and the integrated fusion of four components of molybdenum, nickel and carbon support is achieved through laser pulse irradiation technology, and the size-controlled composite nickel-molybdenum-based material is directly synthesized.

Benefits of technology

It has achieved efficient catalytic water decomposition under alkaline conditions to produce hydrogen, maintain the stability of structural and chemical properties for a long time, significantly improve the catalytic efficiency of the electrocatalyst, and provides an alternative to non-precious metal carbon-supported high-efficiency catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506947A_ABST
    Figure CN119506947A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material science and the technical field of electro-catalysis hydrogen production, and particularly relates to a carbon-supported molybdenum-nickel-based electrocatalyst capable of being used for water electrolysis hydrogen evolution reaction in an alkaline medium and preparation of the carbon-supported molybdenum-nickel-based electrocatalyst. The catalyst is prepared through a laser irradiation process, a carbon-supported molybdenum-nickel-based electrocatalyst is taken as a catalytic activity center, hydrogen can be efficiently prepared by electrolyzing water in an alkaline medium, and the preparation process is wide in raw material source, low in price, mature and stable in process, simple to operate, high in controllability and suitable for large-scale production and industrial hydrogen production by electrolyzing water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patented technology relates to the fields of materials science and water electrolysis catalysis, and in particular refers to an electrode material for efficient water decomposition and hydrogen production in an alkaline environment, which is a carbon-supported molybdenum-nickel-based catalyst, and includes its manufacturing process and practical application method. Background Art

[0002] In the context of global energy transformation, hydrogen energy is highly praised for its wide availability, high energy yield and environmental purity (only water is produced as a combustion byproduct, and there is no greenhouse gas emission), and is regarded as an effective alternative to fossil fuels. Despite this, the manufacturing process of hydrogen remains the main obstacle to its wider application. At present, industrial hydrogen production mainly relies on methods such as petroleum catalytic cracking and natural gas steam reforming, which have not yet fully met the energy strategy goal of "environmental sustainability" in terms of environmental impact and resource utilization efficiency. Fortunately, with the rapid development of renewable energy power generation technologies such as solar, wind and geothermal energy, as well as the continuous improvement of power grid facilities, water electrolysis hydrogen production technology has gradually demonstrated its advantages of high efficiency and environmental friendliness, and is considered to be an ideal choice for achieving industrial-scale hydrogen production. However, the development of electrocatalysts with excellent performance, reliable operation and economic feasibility remains a core challenge to promote the advancement of this technology.

[0003] In the field of water electrolysis for hydrogen production, electrocatalysts based on precious metals such as platinum are widely recognized for their excellent performance. However, the high cost and limited availability of these materials limit their potential for application in large-scale industrial hydrogen production and hinder the widespread promotion of hydrogen production technology. Therefore, the development of economical and efficient non-precious metal electrocatalysts is crucial to promote the innovation of hydrogen production technology. Recent research progress has shown that some non-precious metal elements, such as composites of molybdenum and nickel, have high activity and reliability in catalyzing water decomposition for hydrogen production. Despite these advances, the current synthesis technology of these materials still faces challenges, such as complex preparation processes and the need for additional binding materials to ensure bonding with electrodes. These factors limit their application in industrial production and are more suitable for laboratory-scale preparation. In addition, the catalytic performance of low-loaded precious metal molybdenum-nickel-based materials has not yet reached a level that can completely replace precious metal catalysts, so they still need to be improved in commercial applications. Summary of the invention

[0004] The core goal of the present invention is to develop a new type of water electrolysis hydrogen production electrode, which uses a carbon-supported molybdenum-nickel-based catalyst as its main catalytic active component. Thanks to the wide availability and low cost of its raw materials, this electrode can achieve efficient catalytic reactions under alkaline conditions and maintain the stability of its structure and chemical properties for a long time, making it a preferred solution for industrial-scale water electrolysis hydrogen production.

[0005] Compared with the prior art, the beneficial effect of the present invention is that the carbon support solution provided by the present invention can effectively prevent the agglomeration and deactivation of molybdenum and nickel active centers, and ensure the stability of long-term electrocatalytic hydrogen production. The preparation process of the present invention shows innovation and practicality, and its characteristics are the maturity and stability of the technical process, coupled with the convenience of operation and high adjustability, making it an ideal choice for large-scale manufacturing.

[0006] This patented technology describes a method for preparing a carbon-supported molybdenum-nickel-based electrocatalytic hydrogen evolution catalyst, and its detailed preparation steps include:

[0007] (1) 0.1-20 g (1-10 g, 2-8 g) of a nickel source and 1 g of a molybdenum source are respectively dissolved in 100 mL of a solvent to form two separate solutions; the two solutions are respectively stirred for 1-24 h (1-15 h, 2-8 h) at a temperature range of 20-100 ° C (20-50 ° C, 25-30 ° C);

[0008] (2) The two pre-prepared solutions are mixed and purged with an inert atmosphere (Ar, N2) gas, stirred, and injected into a closed reaction cell with a transparent light window, and 10-200 mL (50-200 mL, 100-150 mL) of a carbonaceous carrier suspension is pumped in at the same time, and laser pulse irradiation with a wavelength of 100-600 nm (150-500 nm, 200-400 nm), a pulse interval of 1-100 ns (1-50 ns, 10-30 ns), and a time of 1-10 h (2-7 h, 3-6 h) is performed through the light window at 50-100 ° C (60-90 ° C, 70-80 ° C);

[0009] (3) After the laser pulse irradiation is completed, the solvent is evaporated and removed to obtain a carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst.

[0010] Preferably, the soluble salt of molybdenum in step (1) is one or more of ammonium dimolybdate, ammonium tetramolybdate, and ammonium paramolybdate. The soluble salt of nickel in step (1) is one or more of nickel chloride, nickel nitrate, and nickel acetate. The alcohol in step (1) is one or more of methanol and ethanol. The carbonaceous precursor in step (2) is one or more of conductive carbon black, porous carbon, and acetylene black.

[0011] The principle mechanism of this patented technology is based on: under the drive of laser irradiation, molybdenum salt, nickel salt and carbonaceous carrier are mixed at the molecular level, nucleation and growth are formed inside the pores of the carrier, and then a carbon-supported molybdenum-nickel-based electrocatalyst with specific spatial confinement is directly formed in the laser irradiation atmosphere. In the laser irradiation-assisted carbon carrier mixing stage, the pore structure of the carbon carrier not only guides the formation of molybdenum-nickel alloy, but also regulates the size of the alloy particles, while giving the final product a porous carbon framework, significantly increasing the active surface area of ​​the electrocatalytic reaction, and facilitating the rapid release of hydrogen after generation. The synergistic effect of molybdenum and nickel precursors, carbon sources and laser irradiation creates this unique structure, giving the electrocatalyst excellent hydrogen production activity and long-term stability in an alkaline environment.

[0012] The catalyst is prepared through a laser irradiation process, with a carbon-supported molybdenum-nickel-based electrocatalyst as the catalytic active center. It can efficiently electrolyze water to produce hydrogen in an alkaline medium. The raw materials required for its preparation process are widely available, inexpensive, the process is mature and stable, the operation is simple, and the controllability is strong. It is suitable for large-scale production and industrial electrolysis of water to produce hydrogen.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The innovative technology described above realizes the integrated fusion of four components, molybdenum, nickel and carbon carrier, through laser irradiation process, and directly synthesizes composite nickel-molybdenum-based materials with controlled size. This process is very suitable for industrial-scale production due to its easy availability of raw materials, low cost, mature technology, convenient operation and strong controllability.

[0015] 2. This technology forms an electronic configuration that surpasses precious metals through the combination of molybdenum and nickel assisted by high-energy laser irradiation, significantly improving the catalytic efficiency of electrocatalysts, and providing an alternative to non-precious metal carbon-loaded high-efficiency catalysts for water electrolysis hydrogen production technology in alkaline environments.

[0016] 3. By compounding the porous carbon-based material with molybdenum-nickel metal under high-energy laser irradiation, the present invention avoids the use of additional coordination solvents and can accurately control the size of the active components, thereby significantly enhancing the structural stability of the electrocatalyst electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0018] Figure 1 Powder XRD diffraction patterns of carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b).

[0019] Figure 2 The scanning electron microscope images and particle size distribution diagram of carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b);

[0020] in Figure 2 (a) and (b) are the scanning electron microscope images and particle size distribution diagrams of NiMo. Figure 2 (c) and (d) are the scanning electron microscope images and particle size distribution diagrams of NiMo-a. Figure 2 (e) and (f) are the scanning electron microscope images and particle size distribution diagrams of NiMo-b.

[0021] Figure 3 These are the test results of the hydrogen evolution activity in water electrolysis of carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b) and commercial platinum-carbon (20% Pt-C) materials.

[0022] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Figure 1 The powder XRD diffraction pattern of carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b) shows that the carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b) all have obvious peaks of molybdenum-nickel alloy. Figure 2 The scanning electron microscope images and particle size distribution diagrams of carbon-supported molybdenum-nickel materials (NiMo, NiMo-a, NiMo-b) show that Figure 2 The average particle size of NiMo is 14.98 nm, the average particle size of NiMo-a is 16.16 nm, and the average particle size of NiMo-b is 13.88 nm. Figure 3 The electrolytic hydrogen evolution activity test results of carbon-supported molybdenum nickel materials (NiMo, NiMo-a, NiMo-b) and commercial platinum carbon (20% Pt-C) materials show that at 100mA / cm 2 At a current density of , the overpotential of NiMo is 0.196 Vvs RHE, the overpotential of NiMo-a is 0.180 Vvs RHE, and the overpotential of NiMo-b is 0.189 Vvs RHE, which are closer to 0 Vvs RHE than the overpotential of commercial 20% Pt-C (-0.215 Vvs RHE), proving that NiMo, NiMo-a, and NiMo-b synthesized by laser irradiation have better alkaline water electrolysis hydrogen production ability than commercial Pt-C catalysts.

[0025] Example 1

[0026] A method for preparing a carbon-supported molybdenum-nickel electrocatalytic hydrogen evolution material is carried out according to the following steps.

[0027] 1.32g of nickel nitrate and 1g of ammonium dimolybdate were dissolved in 100mL of water solvent to form two independent solutions. The two solutions were stirred for 2h at a temperature range of 25°C. Subsequently, the two pre-prepared solutions were mixed and purged with Ar, stirred, injected into a closed reaction cell with a transparent light window (quartz light window in this case), and 100mL of conductive carbon black ethanol suspension (2mg / mL) was pumped in at the same time, and laser pulse irradiation with a wavelength of 248nm, a pulse interval of 5ns, and a time of 1h was performed through the light window at 25°C. After the laser pulse irradiation was completed, the solution was subjected to a rotary evaporation treatment at a temperature of 55°C for 3h to volatilize and remove the solvent to obtain a carbon-supported nickel-molybdenum-based electrolytic water hydrogen evolution catalyst (NiMo).

[0028] The obtained carbon-supported molybdenum nickel-based water electrolysis hydrogen evolution catalyst was tested by inductively coupled plasma spectroscopy and proved to contain 70wt% NiMo alloy and 30wt% carbonaceous carrier.

[0029] Figure 1 The XRD spectrum of the carbon-supported molybdenum-nickel material (NiMo) in the experiment has a significant peak of NiMo alloy, which proves that NiMo is fully mixed in the pores of the conductive carbon black and the NiMo alloy is formed under the driving force of laser irradiation. Figure 2 (a) and Figure 2 As can be seen in (b), the average particle size of carbon-supported molybdenum-nickel material (NiMo) is 14.98 nm, proving that this method can effectively prevent the agglomeration of the alloy and ensure the exposure of active sites.

[0030] The electrocatalytic hydrogen evolution performance of the synthesized carbon-supported molybdenum nickel material (NiMo) was evaluated. The specific test procedure is as follows: a three-electrode system was used for testing, with the NiMo material as the working electrode, a graphite electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. All water electrolysis tests were carried out on the electrochemical testing equipment of Chenhua CHI660e, and the electrolyte used in the test was a 0.1M KOH aqueous solution. In the linear sweep voltammetry test, the scan rate was set to 10mV / s, iR compensation was performed on all electrode potentials, and they were converted into the relative potential of the reversible hydrogen electrode (RHE).

[0031] The process of preparing the NiMo working electrode is as follows:

[0032] (1) First, weigh 10 mg NiMo into a weighing bottle;

[0033] (2) Then, 100 μL of nafion solution (mass concentration 5%) and 900 μL of isopropanol solution (volume ratio of water to isopropanol is 1:2) were measured and added to the weighing bottle in (1);

[0034] (3) Ultrasonic dispersion at a temperature below 25° C. for 1 h to obtain a catalyst dispersion slurry;

[0035] (4) Take 5 μL of catalyst slurry and apply it on the surface of glassy carbon electrode (effective area is 0.19625 cm 2 ), dried naturally, the catalyst loading on the electrode surface is 0.255 mg / cm 2 , and finally electrochemical testing can be carried out.

[0036] like Figure 3 As shown in Figure 2, NiMo exhibits extremely high hydrogen evolution activity in alkaline media, with a current density of 100 mA / cm 2 Under the above conditions, the overpotential is 0.196 V vs RHE, which is closer to 0 V vs RHE (the closer the overpotential is to 0 V vs RHE, the better the performance), compared with the overpotential (-0.215 V vs RHE) of commercial 20 wt% Pt-C (the preparation of Pt 20 wt% Pt-C working electrode is consistent with that of NiMo working electrode). This proves that NiMo synthesized by laser irradiation has better alkaline water electrolysis hydrogen production ability than commercial Pt-C catalyst.

[0037] Example 2

[0038] A method for preparing a carbon-supported molybdenum-nickel-based electrocatalytic hydrogen evolution material is carried out according to the following steps.

[0039] 3.62g of nickel nitrate and 1g of ammonium dimolybdate were dissolved in 100mL of water solvent to form two independent solutions. The two solutions were stirred for 2h at a temperature range of 25°C. Subsequently, the two pre-prepared solutions were mixed and purged with Ar, stirred, injected into a closed reaction cell with a transparent light window (quartz light window in this case), and 150mL of conductive carbon black ethanol suspension (2mg / mL) was pumped in at the same time, and laser pulse irradiation with a wavelength of 340nm, a pulse interval of 10ns, and a time of 3h was performed through the light window at 25°C. After the laser pulse irradiation was completed, the solution was subjected to a rotary evaporation treatment at a temperature of 55°C for 3h to volatilize and remove the solvent to obtain a carbon-supported nickel-molybdenum-based electrolytic water hydrogen evolution catalyst (NiMo-a).

[0040] The obtained carbon-supported molybdenum nickel-based water electrolysis hydrogen evolution catalyst was tested by inductively coupled plasma spectroscopy and proved to contain 62wt% NiMo alloy and 38wt% carbonaceous carrier.

[0041] Figure 1The XRD spectrum of the carbon-supported molybdenum-nickel material (NiMo-a) has a significant peak of NiMo alloy, proving that NiMo is fully mixed in the pores of the conductive carbon black and the NiMo alloy is formed under the driving force of laser irradiation. Figure 2 (c) and Figure 2 As can be seen in (d), the average particle size of carbon-supported molybdenum-nickel material (NiMo-a) is 16.16 nm, proving that this method can effectively prevent the agglomeration of the alloy and ensure the exposure of active sites.

[0042] The electrocatalytic hydrogen evolution performance of the synthesized carbon-supported molybdenum nickel material (NiMo-a) was evaluated, and the specific test procedure was the same as that of Example 1. The working electrode preparation method was the same as that of Example 1.

[0043] like Figure 3 As shown in Figure 2, NiMo-a exhibits extremely high hydrogen evolution activity in alkaline media, with a current density of 100 mA / cm 2 Under the condition of low overvoltage, the overpotential is 0.180 V vs RHE, which is closer to 0 V vs RHE than the overpotential of commercial 20 wt% Pt-C (-0.215 V vs RHE), proving that NiMo-a synthesized by laser irradiation has better hydrogen production ability in alkaline water electrolysis than commercial Pt-C catalyst.

[0044] Example 3

[0045] A method for preparing a carbon-supported molybdenum-nickel-based electrocatalytic hydrogen evolution material is carried out according to the following steps.

[0046] 15.21g of nickel nitrate and 1g of ammonium dimolybdate were dissolved in 100mL of water solvent to form two independent solutions. The two solutions were stirred for 2h at a temperature range of 25°C. Subsequently, the two pre-prepared solutions were mixed and purged with Ar, stirred, injected into a closed reaction cell with a transparent light window (quartz light window in this case), and 200mL of conductive carbon black ethanol suspension (2mg / mL) was pumped in at the same time, and laser pulse irradiation with a wavelength of 550nm, a pulse interval of 40ns, and a time of 8h was performed through the light window at 25°C. After the laser pulse irradiation was completed, the solution was subjected to a rotary evaporation treatment at a temperature of 55°C for 3h to volatilize and remove the solvent to obtain a carbon-supported nickel-molybdenum-based electrolytic water hydrogen evolution catalyst (NiMo-b).

[0047] The obtained carbon-supported molybdenum nickel-based water electrolysis hydrogen evolution catalyst was tested by inductively coupled plasma spectroscopy and proved to contain 77wt% NiMo alloy and 23wt% carbonaceous carrier.

[0048] Figure 1The XRD spectrum of the carbon-supported molybdenum-nickel material (NiMo-b) has a significant peak of NiMo alloy, proving that NiMo is fully mixed in the pores of conductive carbon black and NiMo alloy is formed under the driving force of laser irradiation. Figure 2 (e) and Figure 2 As can be seen in (f), the average particle size of carbon-supported molybdenum-nickel material (NiMo-b) is 13.88 nm, proving that this method can effectively prevent the agglomeration of the alloy and ensure the exposure of active sites.

[0049] The electrocatalytic hydrogen evolution performance of the synthesized carbon-supported molybdenum nickel material (NiMo-b) was evaluated, and the specific test procedure was the same as that of Example 1. The working electrode preparation method was the same as that of Example 1.

[0050] like Figure 3 As shown in Figure 2, NiMo-b exhibits extremely high hydrogen evolution activity in alkaline media, with a current density of 100 mA / cm 2 Under the condition of low overvoltage, the overpotential is 0.189 V vs RHE, which is closer to 0 V vs RHE than the overpotential of commercial 20 wt% Pt-C (-0.215 V vs RHE), proving that NiMo-b synthesized by laser irradiation has better alkaline water electrolysis hydrogen production ability than commercial Pt-C catalyst.

[0051] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst, characterized in that: The preparation steps are as follows: (1) dissolving 0.1-20 g (preferably 1-10 g, more preferably 2-8 g) of a nickel source and 1 g of a molybdenum source in 5-500 mL (preferably 20-300 mL, more preferably 70-100 mL) of a solvent to form two separate solutions; stirring the two solutions for 1-24 h (preferably 1-15 h, more preferably 2-8 h) at a temperature range of 20-100° C. (preferably 20-50° C., more preferably 25-30° C.); (2) mixing the two pre-prepared solutions and purging with an inert atmosphere (vk: Ar and / or N2), stirring, injecting into a closed reaction cell with a transparent light window, and simultaneously pumping in 10-200 mL (preferably 50-200 mL, more preferably 100-150 mL) of a carbonaceous carrier suspension, and irradiating with a laser pulse having a wavelength of 100-600 nm (preferably 150-500 nm, more preferably 200-400 nm) and a pulse interval of 1-100 ns (preferably 1-50 ns, more preferably 10-30 ns) for a time of 1-10 h (preferably 2-7 h, more preferably 3-6 h) through the light window at 50-100 ° C (preferably 60-90 ° C, more preferably 70-80 ° C); (3) After the laser pulse irradiation is completed, the solvent is evaporated and removed to obtain a carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst.

2. The preparation method according to claim 1, characterized in that: The molybdenum source in step (1) is a soluble salt of molybdenum, which is one or more of ammonium dimolybdate, ammonium tetramolybdate, and ammonium paramolybdate; The nickel source in step (1) is a soluble salt of nickel, which is one or more of nickel chloride, nickel nitrate and nickel acetate; In step (1), the solvent is one or more of alcohols or water, and the alcohol is one or more of methanol or ethanol; The carbonaceous carrier in step (2) is one or more of conductive carbon black, porous carbon, and acetylene black; the solvent of the suspension is one or more of methanol, ethanol, and water, with a concentration of 0.1-10 mg / mL (preferably 1-10 mg / mL, more preferably 2-7 mg / mL); The solution is subjected to a rotary evaporation treatment at 20-70°C (preferably 30-60°C, more preferably 40-50°C) for 1-10 h (preferably 1-5 h, more preferably 2-4 h) to remove the solution.

3. A carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst prepared by the method described in any one of claims 1-2.

4. An application of the carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst according to claim 3, characterized in that: An electrocatalytic hydrogen evolution electrode is prepared using the carbon-supported molybdenum-nickel-based water electrolysis hydrogen evolution catalyst as an active component. The electrocatalytic hydrogen evolution electrode is used as a cathode to electrolyze water in an alkaline medium to produce hydrogen.

5. The use according to claim 4, characterized in that The working electrode carrier of electrocatalytic hydrogen evolution is one of carbon paper and nickel foam glassy carbon electrode, with an area of ​​0.001-1cm 2 , carbon-supported molybdenum-nickel material loading 0.1-5mg / cm 2 ; The alkaline medium in the test system is one or more of potassium hydroxide or sodium hydroxide solution, and its concentration is 0.01-10 mol / L; the reference electrode and the counter electrode in the three-electrode system are one or more of Ag / AgCl, Hg / HgO, Pt sheet, Pt wire, and graphite rod; the electrochemical workstation brand is one of Chenhua, Koster, Pine, Biologic or auto-lab; the test results are all based on the Nernst equation (E RHE =E Ag / AgCl +0.0592×pH+0.197) for reversible hydrogen electrode (RHE) calibration, where pH is the value measured in alkaline medium.

Citation Information

Patent Citations

  • High-catalytic-activity amorphous metal oxide hydrogen evolution electrode and preparation method thereof

    CN104894595A

  • Preparation method of mesoporous nitrogen-doped graphene-loaded molybdenum disulfide synthesized by laser irradiation and application of mesoporous nitrogen-doped graphene-loaded molybdenum disulfide in electrocatalytic hydrogen production

    CN110586156A

  • High-activity large-size water electrolysis hydrogen evolution electrode and pulse laser preparation method thereof

    CN114045505A

  • Self-supporting MoNi4 / Mo2C heterojunction hydrogen evolution catalyst and preparation method thereof

    CN118308736A

  • Method for preparing high-hydrogen-evolution nickel-molybdenum electrode surface through femtosecond laser nanocrystallization

    CN118905439A